"Sound attacks": a case report of migraine with hearing aura - Catharino, Antonio Marcos da Silva (2021)
IntroductionMigraine with aura is less frequent than the subtype form without aura. Normally, auras are typically manifested visual symptoms, but it is possible to have an auditory and olfactory complains as aura symptomatology.Case reportAn 8-year-old boy with family cases of migraine, complained of auditory hallucination episodes, since he was 5 years-old, with a duration of 10 to 20 minutes, followed by cure with intense photophobia and nausea. He called these episodes as "sound attacks". The frequency of the crises ranges from 4 to 5 episodes per month, with the maximum of 11 episodes in one month.Neurological examination was normal. He performed angio-MRI of skull and EEG, without any changes. Treatment was initiated with 250 mg sodium divalproate at night with reduction of events, already in the first month, for 2 to 3 episodes per month. The medication was adjusted for 500 mg of sodium divalproate with a good result, not presenting new episodes in the last 2 months.ConclusionWe report a case of migraine crises preceded by auditory aura, in a boy of 8 years. This is a rare and extremely interesting presentation of migraine, with great improvement after the prophylactic treatment.